2015
DOI: 10.1002/ece3.1504
|View full text |Cite
|
Sign up to set email alerts
|

Does sex‐biased dispersal account for the lack of geographic and host‐associated differentiation in introduced populations of an aphid parasitoid?

Abstract: Host recognition and use in female parasitoids strongly relies on host fidelity, a plastic behavior which can significantly restrict the host preferences of parasitoids, thus reducing the gene flow between parasitoid populations attacking different insect hosts. However, the effect of migrant males on the genetic differentiation of populations has been frequently ignored in parasitoids, despite its known impact on gene flow between populations. Hence, we studied the extent of gene flow mediated by female and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…The diversity of the studied populations, after CL2 and CL5, followed an expected pattern of decreasing diversity, according to the length of time in rearing and bottlenecks suffered during the transfer of individuals when initiating new laboratory colonies: the field-collected KZ2, its descendants CL3, a mixed of laboratory populations CL4, and finally the three populations that have the longest rearing history USA, NZ and FR. The estimated diversity of the field population in Kazakhstan was lower than the diversity estimated for other parasitoids, such as N. melanocephalus and A. ervi (Anton et al, 2007, Zepeda-Paulo et al, 2015. This could be because our collection was made in a small isolated patch of an old abandoned apple orchard, which still remains in the outskirts of Almaty, a city that has grown rapidly in the last ten years.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The diversity of the studied populations, after CL2 and CL5, followed an expected pattern of decreasing diversity, according to the length of time in rearing and bottlenecks suffered during the transfer of individuals when initiating new laboratory colonies: the field-collected KZ2, its descendants CL3, a mixed of laboratory populations CL4, and finally the three populations that have the longest rearing history USA, NZ and FR. The estimated diversity of the field population in Kazakhstan was lower than the diversity estimated for other parasitoids, such as N. melanocephalus and A. ervi (Anton et al, 2007, Zepeda-Paulo et al, 2015. This could be because our collection was made in a small isolated patch of an old abandoned apple orchard, which still remains in the outskirts of Almaty, a city that has grown rapidly in the last ten years.…”
Section: Discussionmentioning
confidence: 79%
“…Allelic richness of these populations was on average 2.2 alleles/marker and heterozygosity (He) was 35%. Other studies with parasitoids have shown a higher average allelic richness and heterozygosity: 4.5 alleles/marker and 38% heterozygotes for Neotypus melanocephalus Gmelin (Hymenoptera: Ichneumonidae) (Anton et al, 2007), and 5.2 alleles/marker and 63% heterozygotes for Aphidius ervi (Haliday) (Hymenoptera: Braconidae) (Zepeda-Paulo et al, 2015). The highest estimated diversity was from the laboratory mixed population CL2, which was formed by crossing insects collected in two different regions in the area of origin.…”
Section: Discussionmentioning
confidence: 90%
“…Behavioral experiments using the same laboratory populations from which the individuals of our transcriptome experiment were taken, showed that A. ervi collected from different aphid species ( A. pisum and S. avenae ) and host-races of the pea aphids (pea versus alfalfa) differed in several infectivity traits (host preference) but not in virulence (fitness) ( Zepeda-Paulo et al, 2013 ). This is despite the lack of any detectable genetic structuring in Chilean A. ervi natural populations collected from different aphid hosts species in the field ( Daza-Bustamante et al, 2002 ; Zepeda-Paulo et al, 2015 ). The absence of genetic differentiation is explained by the very recent (1970ies) and single introduction event of A. ervi as a biological control agent for aphid pests in Chile ( Zepeda-Paulo et al, 2016 ; Zúñiga et al, 1986 ).…”
Section: Discussionmentioning
confidence: 94%
“…These results suggest that the preference for the natal host (i.e., host fidelity) is not under direct selection and those parasitoids may show adaptive phenotypic plasticity ( Daza-Bustamante et al, 2002 ; Zepeda-Paulo et al, 2013 ). Indeed, no host race specific differentiation has been detected in Chilean A. ervi populations ( Zepeda-Paulo et al, 2013 ) and a high gene flow predominantly mediated by male dispersion was found between populations ( Zepeda-Paulo et al, 2015 ). Therefore, phenotypic plasticity should be playing a key role in the observed host fidelity ( Henry, Roitberg & Gillespie, 2008 ; Zepeda-Paulo et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The forewing area was used as a proxy for dispersal ability. In parasitoids, dispersal ability strongly influences the host searching performance of the female and mating success of the male individuals (Zepeda‐Paulo et al., ). Our results underlined that as phenotypic differences between guild members may not express themselves equally across all traits, it is important to study multiple traits.…”
Section: Discussionmentioning
confidence: 99%